Reveromycins A and B from Streptomyces sp. 3–10: Antifungal Activity against Plant Pathogenic Fungi In vitro and in a Strawberry Food Model System - Lyu, Ang; Liu, Hao; Che, Hongjie; Yang, Long; Zhang, Jing; Wu, Mingde; Chen, Weidong; Li, Guoqing (Frontiers in Microbiology, 2017)
This study was conducted to determine the antifungal activity of the metabolites from Streptomyces sp. 3–10, and to purify and identify the metabolites. Meanwhile, the taxonomic status of strain 3–10 was re-evaluated. The cultural filtrates of strain 3–10 in potato dextrose broth were extracted with ethyl acetate. The resulting crude extract at 1 and 5 μg/ml inhibited growth of 22 species in 18 genera of plant pathogenic fungi and Oomycetes, accounting for 92% of the total 24 tested species, suggesting that it has a wide antifungal spectrum. Two compounds were purified from the crude extract and were identified as reveromycins A and B, which demonstrated high antifungal activity against Botrytis cinerea, Mucor hiemails, Rhizopus stolonifer, and Sclerotinia sclerotiorum under acidic pH conditions. Both the crude extract and reveromycin A from strain 3–10 at 10, 50, and 100 μg/ml showed high efficacy in suppression of strawberry fruit rot caused by the above-mentioned four pathogens. The efficacy was comparable to that of corresponding commercial fungicides (pyrimethanil, captan, dimetachlone) used in management of these pathogens. Morphological, physiological, and phylogenetic characterization showed that strain 3–10 is closely related to Streptomyces yanglinensis 1307T, representing a novel phylotype in that species. This study reported a new strain with reveromycins-producing capability. The finding is important for further exploitation of reveromycins for agricultural use.